ACCEPTANCE OF PAYMENT SYSTEM ADMINISTRATION STUDENTON 89 SENIOR HIGH SCHOOL JAKARTA - Yayat Yayat; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2002)
Writing is about the problems that arise in student payment revenue administration system. The author proposes a payment administration system to solve problems in revenue administration system of payment such students. This system is used to improve the effectiveness and quality of work of the administration part of the payment receipt.This system stores data and data processing students' payments into a monthly report. The final part of the writing of programs is attached as a supporter of the administration system.